Vertical seismic profiles: Now just another log? - Dean, Timothy; Constantinou, A.; Cuny, T.; Frignet, B.; Hartog, A.; Kimura, T.; Kolesar, R.; Lane, D.; Lees, G. (2015)
© 2015 SEG.Due to the limited number of receivers employed, acquiring a vertical seismic profile is time consuming and is therefore often excluded from a logging job to save time. The combination of a fiber optic DVS recording system, a GPS-time-based source controller, and an easily adaptable QC and visualization system results in the time required to acquire a simple VSP survey being reduced from hours to minutes. If the data are acquired as part of a conventional logging job then the acquisition does not require any additional well or rig-up time. The results shown here demonstrate that the results acquired with such a system are consistent with conventional VSP tools, even in suboptimal coupling conditions (a water-filled vertical hole).